3D printed gelatin/hydroxyapatite scaffolds for stem cell chondrogenic differentiation and articular cartilage repair. (17th February 2021) - Huang, Jianghong; Huang, Zhiwang; Liang, Yujie; Yuan, Weihao; Bian, Liming; Duan, Li; Rong, Zhibin; Xiong, Jianyi; Wang, Daping; Xia, Jiang
Abstract : The hUCB-MSC-laden 3D printed gelatin/HAP scaffold effectively repairs knee cartilage defects in a pig model. Abstract : Acute injury of the articular cartilage can lead to chronic disabling conditions because of the limited self-repair capability of the cartilage. Implantation of stem cells at the injury site is a viable treatment, but requires a scaffold with a precisely controlled geometry and porosity in the 3D space, high biocompatibility, and the capability of promoting chondrogenic differentiation of the implanted stem cells. Here we report the development of gelatin/hydroxyapatite (HAP) hybrid materials by microextrusion 3D bioprinting and enzymatic cross-linking as the scaffold for human umbilical cord blood-derived mesenchymal stem cells (hUCB-MSCs). The scaffold supports the adhesion, growth, and proliferation of hUCB-MSCs and induces their chondrogenic differentiation in vitro . Doping HAP in the gelatin scaffold increases the fluidity of the hydrogel, improves the gelation kinetics and the rheological properties, and allows better control over 3D printing. Implanting the hUCB-MSC-laden scaffold at the injury site of the articular cartilage effectively repairs the cartilage defects in a pig model. Altogether, this work demonstrates the 3D printing of gelatin-based scaffold materials for hUCB-MSCs to repair cartilage defects as a potential treatment of articular cartilage injury.